Analisis Pengaruh Pemerintahan Dengan Algoritma Dan Artificial Intelligence (AI) Terhadap Kepatuhan Wajib Pajak Pada Kpp Pratama Jakarta Mampang Prapatan - Akbari Adha; Rulinawaty Rulinawaty; Faizal Madya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the effect of governance by algorithm and artificial intelligence (AI) on taxpayer compliance at KPP Pratama Jakarta Mampang Prapatan. The results showed that there is a significant influence between government with algorithms and artificial intelligence on taxpayer compliance. In the government variable with the algorithm (X1), the t-count value is 5,491 with a significance level of 0.000, which is smaller than the 5% confidence level. This t-count value (5.491) is greater than the t-table (1.967). This causes the alternative hypothesis (Ha) to be accepted and the null hypothesis (H0) to be rejected, so it can be concluded that there is a significant influence between government and algorithms on taxpayer compliance at KPP Pratama Jakarta Mampang Prapatan. Furthermore, in the artificial intelligence variable (X2), the t-count value is 5.892 with a significance level of 0.001, which is greater than the 5% confidence level. The t-count value (5.463) is also greater than the t-table (1.967). This causes the alternative hypothesis (Ha) to be accepted and the null hypothesis (H0) to be rejected, so it can be concluded that there is a significant influence between artificial intelligence on taxpayer compliance at KPP Pratama Jakarta Mampang Prapatan. The results of the determination test of the Government with Algorithms and Artificial Intelligence can explain the Taxpayer Compliance of KPP Pratama Jakarta Mampang Prapatan by Adjusted R square is 0.774 which means 77.40%, while the remaining 22.60% is influenced by other factors.